Different sizes of position games and official matches in youth professional soccer player - Jose A. Asian-Clemente; Jose Vicente Beltran-Garrido; Bernardo Requena (Biology of Sport)
The objectives of this study were to compare the external load of position games and matches in soccer players and to assess the effect of different pitch sizes on position games in relation to competition. Twenty-five players (age: 21.9±1.9 years; height: 177.9±5.2 cm; weight: 75.5±4.8 kg) were evaluated during 37 official matches and 18 position games classified according to their pitch sizes: Small, Medium and Large (50.8±6.6 m², 80.5±4.6 m² and 115.9±25.2 m² relative area per player, respectively). Using a GPS system, total distance (DC), DC > 21 km·h −1 , peak speed, and maximal accelerations and decelerations lower and higher than 3 m·s −2 (Acc <3 ; Acc >3 ; Dec <3 and Dec >3 , respectively) were recorded. Mixed model analyses were used to compare the effects of the game condition and of space dimensions on the dependent parameters. During the position games, lower values of DC, DC > 21 km·h −1 , peak speed, Acc <3 , Dec <3 , maximal accelerations and maximal decelerations were reported than in matches. Position games showed higher values than matches for the Acc >3 and Dec >3 . All analysed variables reached statistical significance (all p 21 km·h −1 , peak speed, Acc <3 , Dec <3 , maximal accelerations and maximal decelerations, but significantly higher Acc >3 and Dec >3 (all p < 0.05) than matches. The data showed that position games of 9 vs. 9 + 2 with a relative area per player ≤ 115.9 m² present a different external load than matches.